A Study of the Mystery of Plant Mythology in Masnavi-i Ma`navi - hojat abasi (Matn/Pizhūhī-i Adabī, 2008)
Owing to the extensive implication of myths underlying the original work of Masnavi-i Ma`navi, this exquisite peculiarity prompts us to put much insight and scrutiny into studying this work compared with other ones. The attachment between this work and other mystical worlds has led to the formation of a multi-layered and comprehensive text that establishes a mysterious atmosphere in the work, the interpretation of which elevates us to go beyond the superﬁcial commonalities. Myths of the tree of life, tree of Kharrub, and the botanical origin of man, which have been referred to several times in Masnavi, are amongst the ones swing the text from side to side and engaging it with the primeval ontology of human being. In the present research, putting these three myths along with other materials and expanding on their relations to other mythologies, we have tried to give a sound realization of these myths.